Does ASEAN climate policy pay sufficient attention to public transportation? - Malin Øren Aldal; Indra Overland (Discover Sustainability)
Abstract Expansion of public transportation is a climate mitigation measure with many potential co-benefits and positive externalities: reduced congestion, lower air and noise pollution, improved road safety, and poverty alleviation. Most of the member states of the Association of Southeast Asian Nations (ASEAN) face serious challenges in all these areas. This paper therefore investigates how much emphasis the ten ASEAN member states are putting on public transportation compared to other areas in their climate policies. As the empirical basis for the analysis, a dataset was compiled of all targets and measures in the nationally determined contributions (NDCs) of the ASEAN countries. The analysis shows that only 2.2% of the sectoral mitigation targets and measures in the ASEAN NDCs relate to public transportation, and six of the ten NDCs have no public transportation targets or measures. These numbers are surprisingly low considering the challenges related to transportation in the ASEAN megacities and the numerous co-benefits of resolving them. Using the Avoid-Shift-Improve framework for sustainable transportation, the study finds that almost three fourths of the transportation targets and measures in the NDCs belong to the “Improve” category. This indicates that there is potential to further develop policies to “Shift” travel to public transportation and integrate them into the next round of NDC updates.